PERBANDINGAN JUMLAH LEUKOSIT PADA PENGGUNA ROKOK ELEKTRIK DAN ROKOK KONVENSIONAL - Uray Dinda Saputri; Fadli Sukandiarsyah; Khairul Bariyah (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
Smoking has become a habit that often occurs in everyday life for people in Indonesia. There are many alternative ways that can be done on tobacco cigarettes. This type of electric cigarette is one of the newest phenomena to replace tobacco cigarettes. The side effect of cigarette smoke is that we can see an inflammatory response through an increase in the number of leukocytes in the peripheral blood. This study aims to determine the comparison of the number of leukocytes in electric cigarette users and conventional cigarettes. This type of research is analytic observational with cross sectional research design. The sampling technique used purposive sampling with a total sample of 30 electric smokers and 30 conventional smokers. Research by conducting the Mann-Whitney test on a comparison of the number of leukocytes in users of electric cigarettes and conventional cigarettes with a significant value of 0.05 obtaining P = 0.717. There is no difference in the number of leukocytes in the use of electric cigarettes and conventional cigarettes. the conclusion is the conclusion of the results and discussion presented in the results and discussion chapter.